Impact of Oil Palm Plantation on Economy and Environment in Bengkulu Province - Herlina, Nia; Wahyuni, Herpita (Jurnal Mamangan, 2022)
Oil palm, viewed from the economic aspect, can build a financial center to support regional economic growth. This study aims to determine the impact of oil palm plantations on the economy and the environment in Bengkulu Province. This study uses descriptive qualitative research using sources from various previous studies. It is equipped with multiple literature or literature reviews that will answer the research results on the impact of oil palm plantations on the economy and the environment. The study results reveal that oil palm plantations in Bengkulu Province improve people's welfare, create jobs, and contribute to regional development in Bengkulu Province. Extensive oil palm plantations hurt the environment, which results in regular flooding due to forest encroachment and large-scale opening of plantations so that forests and land cover are damaged; this results in significant surface runoff of rainwater and rainwater infiltration. Small scale causes an imbalance due to considerable runoff triggering erosion and land degradation. Facing this problem by maintaining forest and spatial planning by continuing reforestation, especially in the upstream area to keep it stable and handling the waste system and urban systems must be integrated, flood-prone points can be overcome.